Xenografting / Xeno Bone Grafting and Synthesis of Hydroxyapatite from Bovine and Camel Bone - Adaghaies, Hussain Saleh (International Journal of Innovative Research in Medical Science, 2020)
Development of artificial bone grafts has increasingly progressed in the last few years. Significant progress has thereby been made in development, preclinical testing and clinical use of different matrices. In addition to complete synthetically manufactured products, xenografts based on bovine material are in wide spread clinical use. Possible transmission of prions causing bovine spongiform encephalopathies and Creutzfeldt-Jakob disease give the background for discussing the advantages and disadvantages of synthetic versus xenografts. Possible risks using xenografts based on bovine material are discussed. Bone grafts are used as a filler and scaffold to facilitate bone formation and promote wound healing. These grafts are bioresorbable and have no antigen-antibody reaction. These bone grafts act as a mineral reservoir which induces new bone formation. In this review, we will present up to date knowledge about xenografts used in the field of dentistry and I will tray to make this study as firest step for new product of xeno-grafting in future from my nature in Arabian land of Saudi Arabia and produce it from new source ( camel bone material comparing to bovine bone material)